2006
DOI: 10.1364/oe.14.009594
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of coupling to symmetric and antisymmetric cladding modes in arc-induced long-period fiber gratings

Abstract: The symmetry of cladding modes excited in microbend and arcinduced long-period fiber gratings is investigated. An optimization technique is developed to determine the fiber parameters and to associate grating resonances with cladding modes of a particular symmetry. Using this optimization procedure, we show that the gratings induced in a standard fiber by arc discharges and microbends couple light to the antisymmetric cladding modes. In the case of a boron-germanium codoped fiber, the cladding modes excited by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 9 publications
5
40
0
Order By: Relevance
“…For the simulation, we assumed that the formation of the grating is due to the core-shift mechanism and that during diffusion the refractive index profile follows a "top-hat" shape which is valid for the beginning of the diffusion process (changes of the order of 1%), that is, Δn dif = (R co / R dif ) 2 × Δn co-cl where R dif and Δn dif are respectively, the new core radius and the new core-cladding index difference during the diffusion process. The initial values of R co = 4.18 mm and Δn co-cl = 4.85 × 10 − 3 (at 1550 nm), which are close to the parameters of the standard fibre, have been obtained by taking into account the effect that the arc discharge has on the fibre properties [13] and they have been used to fit the spectrum in Ref. [3].…”
Section: Resultsmentioning
confidence: 99%
“…For the simulation, we assumed that the formation of the grating is due to the core-shift mechanism and that during diffusion the refractive index profile follows a "top-hat" shape which is valid for the beginning of the diffusion process (changes of the order of 1%), that is, Δn dif = (R co / R dif ) 2 × Δn co-cl where R dif and Δn dif are respectively, the new core radius and the new core-cladding index difference during the diffusion process. The initial values of R co = 4.18 mm and Δn co-cl = 4.85 × 10 − 3 (at 1550 nm), which are close to the parameters of the standard fibre, have been obtained by taking into account the effect that the arc discharge has on the fibre properties [13] and they have been used to fit the spectrum in Ref. [3].…”
Section: Resultsmentioning
confidence: 99%
“…It is worth to observe that an additional benefit of the electric arc technique lie in the fact that it is based on a very simple fabrication procedure needing inexpensive equipment. However it should be also pointed out as a major pitfall of these techniques that the intrinsic asymmetry in the heating process leads to birefringence with consequent polarization dependent losses or coupling to azimuthally asymmetric cladding modes (Rego et al, 2006). C o m i n g b a c k t o t h e a p p l i c a t i o n s o f L P G s a s s e n s o r s w e c a n i d e n t i f y f o u r p h y s i c a l parameters of interest: applied tensile stress can modify the effective indices of core and cladding modes through the elasto-optic effect and the grating period because of elongation ; thermo-optic effect is responsible for the effective index change while thermal expansion for period modification in the case of the temperature changes (Shu et al, 2002); bending breaks the cylindrical symmetry of the waveguide promoting coupling to azhymuthally asymmetric cladding modes that are differently affected in their effective indices depending on the region of the fiber where they are confined (Block et al, 2006); finally the effective indices of cladding modes directly depend on the index contrast between the cladding and the surrounding medium being a boundary condition in the solution of the waveguide equation (Patrick et al 1998).…”
Section: Long Period Gratings: a View Backmentioning
confidence: 99%
“…At the same time, the gratings arc-induced in B/Ge fibres couple the core mode to the symmetric cladding modes as a result of induction of internal stresses (reversible structural rearrangement) [10,11]. The type of modes excited by arc-induced LPFGs in pure-silica-core fibres was not investigated previously.…”
Section: Simulation Of the Grating Spectrummentioning
confidence: 99%
“…Recently, we demonstrated that the periodic microdeformations induced in the fibre core due to temperature gradients in the arc are responsible for the creation of asymmetric gratings in standard fibres [10,11]. In this paper, we investigate the mechanism of formation of gratings in the pure-silica-core fibre inscribed by arc discharges and study the role of periodic microdeformations for this type of fibre.…”
Section: Introductionmentioning
confidence: 99%